Visual and acoustic communication in the Brazilian torrent frog, Hylodes asper (Anura : Leptodactylidae) - Haddad, CFB; Giaretta, A. A. (Herpetologists League, 1999)
We studied the signaling, territorial, and courtship behaviors of the diurnal frog Hylodes asper. Visual and acoustic communication were used during intraspecific interactions involving males, females. and subadults. Hylodes aspcr has a complex visual communication system, of which foot-flagging is the most distinctive display observed in the repertoire of visual signals. The splash zone produced by the waterfalls and torrents creates a high, nearly constant, humidity near the streams, reducing the risk of desiccation which enables the diurnal activity of H. asper. Although the ambient sound pressure levels (SPL), measured at the calling sites, are similar to the SPL of the advertisement calls, the high-pitched calls of H, asper, are spectrally different from the noise produced by the water current. Thus. The ambient noise produced by the water current may not interfere significantly with the acoustic communication of this species. The noise and the nearly constant and high humidity produced by the torrents and waterfalls, along with the availability of Light, probably favored the evolution of contrasting colors and visual communication in H. asper: Males of H, aspcr excavate underwater chambers that are probably used to shelter the eggs and to prevent the clutch from being drifted downstream.
Keywords: Hylodes asper; Anura; Hylodinae; visual communication; acoustic communication; reproductive mode; Atlantic Forest; southeastern Brazil